A two-dimensional buffer valve for heavy-duty vehicles: Design, dynamic modeling, and experimental verification. (June 2023) - Du, Hongwang; Wang, Wenchao; Xiong, Wei
Graphical abstract Focusing on the problems of weak anti-pollution capability and large lateral sliding friction of gears in traditional vehicle cushion valves, this study combined two-dimensional (2D) technology and the concept of pressure torsion transmission and proposed a 2D buffer valve with a fast response, high precision, and strong anti-pollution capability. The structure and working principle of the 2D buffer valve were introduced, and a dynamic model was developed for the 2D buffer valve. The model was jointly solved by Simulink and AMESim, and simulation analyses and experimental research were performed. The research results show that the step response time of the 2D pressure torque transmission buffer valve was approximately 0.024 s, and the maximum overshoot was approximately 7.4%. During the shift buffering process, the maximum deviation was 0.077 MPa, and the steady-state error was 0.018 MPa. The buffer valve proposed in this paper could achieve good control of the clutch oil pressure of the vehicle transmission, thereby improving the buffering performance and shifting quality in heavy-duty vehicles.